ESG Performance, Internal Factors, and Non-Performing Financing in Islamic Banks: Evidence from OIC Countries: Studi Empiris di Negara OKI - Aziz, Alif Fahril; Bayu Arie Fianto (Jurnal Ekonomi Syariah Teori dan Terapan, 2024)
This study aims to examine the effect of internal bank factors and ESG performance on the problematic financing of Islamic banking in OIC countries. This study uses quantitative methods with panel data regression analysis techniques used to test the hypotheses proposed in the study. This study uses data sources of Islamic banks' financial reports taken from Bloomberg database. The results of this study indicate that partially and simultaneously all variables have a significant effect on non-performing financing (NPF). The variables of profitability (ROA), financing growth, and ESG Score show negative significant results which means these variables can reduce the risk of non-performing financing, while the variables of bank capital (CAR), bank provisions (FLP), and previous year's non-performing financing (NPFt-1) show positive significant results which means these variables can increase the risk of non-performing financing. The limitation in this study is that the sample used only consists of 50 Islamic banks in OIC countries. Despite these limitations, the results imply that bank management needs to pay attention to internal bank factors and ESG policies to minimize the risk of non-performing financing. This study contributes to the scientific literature on the relationship between bank internal policies and ESG policies on non-performing financing in Islamic banking in OIC countries..